Cerium oxide nanoparticles in wound care: a review of mechanisms and therapeutic applications - Chen, Shouying; Wang, Yiren; Bao, Shuilan; Yao, Li; Fu, Xiao; Yu, Yang; Lyu, Hongbin; Pang, Haowen; Guo, Shengmin; Zhang, Hongwei; Zhou, Ping; Zhou, Yun (Frontiers in Bioengineering and Biotechnology, 2024)
Skin wound healing is a complex and tightly regulated process. The frequent occurrence and reoccurrence of acute and chronic wounds cause significant skin damage to patients and impose socioeconomic burdens. Therefore, there is an urgent requirement to promote interdisciplinary development in the fields of material science and medicine to investigate novel mechanisms for wound healing. Cerium oxide nanoparticles (CeO2 NPs) are a type of nanomaterials that possess distinct properties and have broad application prospects. They are recognized for their capabilities in enhancing wound closure, minimizing scarring, mitigating inflammation, and exerting antibacterial effects, which has led to their prominence in wound care research. In this paper, the distinctive physicochemical properties of CeO2 NPs and their most recent synthesis approaches are discussed. It further investigates the therapeutic mechanisms of CeO2 NPs in the process of wound healing. Following that, this review critically examines case studies focusing on the effects of CeO2 NPs on wound healing. Finally, it suggests the potential application of cerium oxide as an innovative nanomaterial in diverse fields and discusses its prospects for future advancements.